Association between density of tumor-infiltrating lymphocytes and prognoses of patients with gastric cancer. Issue 27 (July 2018) - Yu, Peng-Cheng; Long, Di; Liao, Cheng-Cheng; Zhang, Sen
Abstract: Introduction: Tumor-infiltrating lymphocytes (TILs) have been shown to be of prognostic significance in patients with gastric cancer. This study aims to investigate the association between density of TILs and prognoses of patients with gastric cancer. Methods: The relative studies of tumor-infiltrating lymphocytes in tumor tissue from patients with gastric cancer were systematically searched from PubMed and Embase until October 31, 2017. The pooled hazard ratios (HRs) and their 95% confidence intervals (95%CI) for overall survival (OS) were estimated. Results: Twenty-nine studies involving 4, 942 patients were included into analyses. Subset of TILs included CD8 +, CD3 +, CD4 +, and FOXP3 + T cell density. Results from meta-analyses revealed that high density of intratumoral CD8 + T cells (HR = 0.77, 95% CI 0.63–0.95) and CD3 + (HR = 0.62, 95% CI 0.49–0.77) were associated with significantly higher OS than those with low density in patients with gastric cancer. Moreover, a larger number of general TILs density also suggested a favorable prognosis (HR 0.75, 95% CI 0.67–0.84). However, patients with high density of intratumoral FOXP3 + T or CD4 + T cells were not statistically associated with higher or lower OS than those with low density (HR 1.41, 95% CI 0.97–2.05; HR = 0.86, 95% CI 0.47–1.57). Sample size and follow-up period seemed to influence study outcomes. Conclusion: The present study revealed that high density of intratumoral CD8 + and CD3 + T cells were associated with better OS in patients with gastric cancer.